2020
DOI: 10.12659/aot.927420
|View full text |Cite
|
Sign up to set email alerts
|

Acute Rejection and Infectious Complications in ABO- and HLA-Incompatible Kidney Transplantations

Abstract: Background Patients receiving ABO-incompatible (ABOi) or human leukocyte antigen (HLA)-incompatible (HLAi) kidney transplantation (KT) require potent immunosuppression and are thus at a higher risk of infectious complications. We evaluated the clinical outcomes of KT stratified by ABO and HLA incompatibilities and identified the factors associated with the clinical outcomes. Material/Methods Recipients who underwent living-related KT between 2012 and 2017 were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…These findings are in parallel with several other studies [23,[29][30][31]. Moreover, age, HLA-incompatible transplantation, and a higher number of HLA mismatches were associated with rejection after transplantation, in agreement with results from previous reports [32][33][34]. Our study indicated that episodes of viral or nonviral infection requiring hospitalization were associated with older age, deceased rather than living donors, female sex, HLA-incompatible and ABO-incompatible kidney transplantation, and ATG rather than basiliximab induction, in accordance with previous studies [32,33,[35][36][37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are in parallel with several other studies [23,[29][30][31]. Moreover, age, HLA-incompatible transplantation, and a higher number of HLA mismatches were associated with rejection after transplantation, in agreement with results from previous reports [32][33][34]. Our study indicated that episodes of viral or nonviral infection requiring hospitalization were associated with older age, deceased rather than living donors, female sex, HLA-incompatible and ABO-incompatible kidney transplantation, and ATG rather than basiliximab induction, in accordance with previous studies [32,33,[35][36][37].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, age, HLA-incompatible transplantation, and a higher number of HLA mismatches were associated with rejection after transplantation, in agreement with results from previous reports [32][33][34]. Our study indicated that episodes of viral or nonviral infection requiring hospitalization were associated with older age, deceased rather than living donors, female sex, HLA-incompatible and ABO-incompatible kidney transplantation, and ATG rather than basiliximab induction, in accordance with previous studies [32,33,[35][36][37]. Because a compromised capacity to repair injury in older kidneys could lead to accelerated immune response and acute rejection, the risks of rejection might be higher in older donor kidney transplantation [38].…”
Section: Discussionsupporting
confidence: 92%
“…CD226 downregulation and high levels of TIGIT were previously described in cancer and chronic viral infections 19 21 . In the same way, we previously found in highly immunosuppressed HLA incompatible kidney transplant recipients known to present a high risk of infectious complications 43 , higher levels of TIGIT expression, compared to ABO-incompatible recipients 25 . TIGIT was also previously identified in kidney biopsies as one of the most specific transcript changes (with other costimulation -related transcript) during pure T-cell mediated rejection, compared with other disease 44 .…”
Section: Discussionsupporting
confidence: 72%
“…Among them, HLA (human leukocyte antigen) is known to be the expression product of human major histocompatibility complex (MHC). The mismatch of HLA is a risk factor to affect kidney allograft function and to increase the chance of rejection [ 31 – 33 ]. For example, Ko et al investigated the clinical outcome of kidney transplantation with ABO and HLA incompatibilities.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Ko et al investigated the clinical outcome of kidney transplantation with ABO and HLA incompatibilities. The result found that ABO and HLA incompatibilities could increase the probability of infection-medicated rejection and influence the overall survival both for patient and graft [ 31 ]. Moreover, HLA donor-specific antibodies could induce inflammation, vessel injury and AMR by binding to vascular endothelial cells of the allograft [ 34 ].…”
Section: Resultsmentioning
confidence: 99%